2016
DOI: 10.1371/journal.pone.0153923
|View full text |Cite
|
Sign up to set email alerts
|

A Moment of Mindfulness: Computer-Mediated Mindfulness Practice Increases State Mindfulness

Abstract: Three studies investigated the use of a 5-minute, computer-mediated mindfulness practice in increasing levels of state mindfulness. In Study 1, 54 high school students completed the computer-mediated mindfulness practice in a lab setting and Toronto Mindfulness Scale (TMS) scores were measured before and after the practice. In Study 2 (N = 90) and Study 3 (N = 61), the mindfulness practice was tested with an entirely online sample to test the delivery of the 5-minute mindfulness practice via the internet. In S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 47 publications
1
30
3
Order By: Relevance
“…An important but understudied question is how much mindfulness practice is needed in order for benefits to emerge [53]. Whilst some studies suggest that just a single meditation session is sufficient to increase state mindfulness [54] and positive affect [55], others suggest that improvements in stress require a minimum of 4 weeks of training [56]. In the present study, participants experienced consecutive increases in self-reported well-being following 10 and 30 days, though the rate of benefit was greatest between baseline and day 10, during which participants completed an average of just 6.21 meditations.…”
Section: Discussionmentioning
confidence: 99%
“…An important but understudied question is how much mindfulness practice is needed in order for benefits to emerge [53]. Whilst some studies suggest that just a single meditation session is sufficient to increase state mindfulness [54] and positive affect [55], others suggest that improvements in stress require a minimum of 4 weeks of training [56]. In the present study, participants experienced consecutive increases in self-reported well-being following 10 and 30 days, though the rate of benefit was greatest between baseline and day 10, during which participants completed an average of just 6.21 meditations.…”
Section: Discussionmentioning
confidence: 99%
“…Single, short-duration (e.g., 5-minute) bouts of mindfulness have previously been shown to enhance perceived state mindfulness. 34 Results from our manipulation check indicate that participants felt they had engaged in mindfulness. As such, we feel comfortable considering mindfulness-related mechanisms to explain the observed findings.…”
Section: Discussionmentioning
confidence: 91%
“…In most cases, mindfulness is defined as a moment-by-moment experience with clear-eyed attention to the working of the mind, body and behaviour [ 25 , 26 ]. The regulation and maintenance of focused attention and awareness lead to an experience of wakefulness called state mindfulness [ 27 , 28 ]. Mindfulness can also be conceptualised as a stable trait assumed to be a part of the personality, which is pronounced differently in individuals and can be increased by regular practice [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The regulation and maintenance of focused attention and awareness lead to an experience of wakefulness called state mindfulness [ 27 , 28 ]. Mindfulness can also be conceptualised as a stable trait assumed to be a part of the personality, which is pronounced differently in individuals and can be increased by regular practice [ 28 ]. Mindfulness means not only perceiving the current moment, but also having a non-judgmental attitude towards it.…”
Section: Introductionmentioning
confidence: 99%